Effects of walking jogging and running program on coronary heart disease risk factors among middle aged men - Ravindran1, K. Suthakar1, B. Annida2, B. Parthiban1*, K. Sekarbabu1, G. (Journal of Experimental Sciences, 2010)
Physical activity helps to lower blood pressure and cholesterol, and helps reduce obesity, symptoms of anxiety and depression, and symptoms of arthritis. It turns out, to acquire many of these health benefits; exercise does not have to be strenuous. Moderate daily physical activity can substantially reduce the risk of developing or dying from type IIdiabetes, and a variety of cardiovascular diseases, such as heart disease, hypertension, and stroke. The present study was designed to find out the effects of walking, jogging and running exercises on coronary heart disease risk factors among middle aged men. Forty middle aged menof teaching and nonteaching staff members belong to the Department of Physical Education and Sports Sciences, Annamalai University was selected as subjects and theiraged group ranges from 35-40 years. Selected subjects were classified into four groups with 10 members each. Group I act as Control, Group II underwent walking, Group III Joggingand Group IVRunning.Â  Exercise programme were given to the training groups for a period of 3 days /week for 12 weeks. The variables selected for this study were body weight, blood glucose and blood pressure(systolic and diastolic).The staff members were trained with the regular schedule timings initiating with the light warm-up, walkingÂ  jogging and running exercise of the concerned group. The intensities were progressively increased at the end of every week. Data were collected and statistically analyzed using ANOVA and DMRT. Results showed that walking, jogging and running significantly reduces the coronary risk factors in middle aged men. It is also observed that better effect was seen in running people when compared to walking and jogging groups at the rate of intensity increased.Thus the study revealed that 12 weeks of running program in middle aged men produced better moderations in cardiac risk factors and retains them healthier life.